Ngala Ulam Tradition from a Socio-Religious Perspective: Study in Kampung Genten, Pasirhuni Hamlet, Laksana Village, Ibun District, Bandung Regency - Aep Saepuloh; Dodo Widarda (International Journal of Science and Society, 2023)
The article explores the Ngala Ulam tradition, a unique cultural practice deeply rooted in socio-religious contexts. The study focuses on the Kampung Genteng, specifically in the Pasirhuni Hamlet, Laksana Village, Ibun District, Bandung Regency. This socio-religious perspective aims to unravel the intricate layers of meaning embedded in the Ngala Ulam tradition. The research employs qualitative methods, including in-depth interviews, participant observation, and document analysis. By delving into the socio-religious aspects, the study unveils the significance of Ngala Ulam beyond its surface practices. It investigates how the tradition interweaves with local beliefs, community bonds, and spiritual elements. The tradition of treating toothaches with the Ngala Ulam method is a result of acculturation between the local community's beliefs and Islam. This is because before Islam entered Kampung Genteng Dusun Pasirhuni, the community had adhered to a hereditary belief in the methods of treating diseases. The presence of Islam did not clash with the local culture; instead, a fusion occurred, with Islam influencing it. This acculturation can be observed in the medium used in the Ngala Ulam practice, namely the use of cangkarud mulud beads produced from the muludan tradition. Additionally, acculturation is evident in the Ngala Ulam practice, incorporating Islamic chants and prayers. The Ngala Ulam tradition illustrates that community knowledge is a social product. The knowledge and beliefs in the Ngala Ulam ritual are products of the Kampung Genteng community. Although modern medical equipment and systems are known to the community, the people's beliefs in traditional, non-rational treatments remain strong. The continued high trust in the Ngala Ulam treatment is reinforced by factors such as the distance and cost associated with accessing modern healthcare facilities like Puskesmas.